ANALYSIS OF THE CAPABILITIES OF BLOCKCHAIN TECHNOLOGY IN DATA MANAGEMENT (Modern education and development, 2025)
This paper discusses the issues of using blockchain technology for user authorization, such as limited scalability, high usage costs, limited interoperability, insufficient protection against cyberattacks, security and privacy issues, limited legal regulation, and low user awareness. The article describes ways to address these challenges, such as improving scalability, optimizing resource usage, developing interoperability standards, employing additional security measures, ensuring data confidentiality, creating new legal norms, and promoting user technical literacy. Using blockchain technology in user authorization can offer significant advantages, but it requires a thorough analysis of the problems, the development of appropriate solutions, and the provision of high levels of security and privacy when working with blockchain networks.